Healthy Leadership in Turbulent Times: The Effectiveness of Health-Oriented Leadership in Crisis - Laura Klebe; Jörg Felfe; Katharina Klug (British Journal of Management, 2021)
Previous research has supported the positive effects of health-oriented leadership (HoL) on follower health. However, effectiveness in times of crisis is unknown. This study examines whether crises weaken or strengthen the positive relationships of health-oriented leadership with follower strain and performance. Effectiveness was tested for (1) follower irritation and performance (extra effort) in smaller crises on the team level with a vignette study (N = 257) and (2) follower exhaustion and performance (task proficiency) during the Covid-19 crisis in a cross-sectional survey study (N = 196). As expected, the results provided evidence for an increase in follower health with higher health-oriented leadership but a decrease in health in crises. The positive relationship between health-oriented leadership and follower health was even stronger in crises. Health-oriented leadership had a positive relationship with job performance in both studies.
Keywords: 650